The sarcolemmal calcium pump 4 is a specific and powerful regulator of pathological cardiac hypertrophy. (22nd September 2015) - Oceandy, D; Mohamed, T; Prehar, S; Zi, M; Baudoin, F; Stanley, P; Cartwright, E; Neyses, L
Abstract : The plasma membrane calcium/calmodulin dependent ATPase (PMCA) ejects calcium from the myocardium but its role in diastolic relaxation is minor. We have therefore been exploring whether PMCA plays a role in signalling. We have shown that the isoform 4b of PMCA (PMCA4b) regulates nitric oxide (NO) signalling from a specific subfraction of cardiac neuronal nitric oxide synthase (nNOS) bound to it via a PDZ domain. Here we investigated whether PMCA4 is differently regulated in human heart failure and whether it is involved in regulating hypertrophic signals. In human failing hearts PMCA4 protein expression was reduced by 60% compared with normal hearts (n = 3, p<0.01). PMCA4 was also downregulated by 25% in hypertrophic mouse hearts following transverse aortic constriction (TAC) (n = 5, p<0.05). To investigate signal transmission by PMCA4 in the hypertrophic process, we subjected PMCA4 knockout (PMCA4 −/− ) mice to TAC for 5 weeks. PMCA4 −/− mice displayed a significantly reduced hypertrophic response compared with wild-type (WT) littermates. (Heart weight/tibia length ratio after TAC, PMCA4 −/− : 6.74 ± 0.33 mg/mm vs WT: 8.34 ± 0.88 mg/mm, p<0.05, n > 10). Echocardiography and left ventricular pressure volume loops revealed that PMCA4 ablation protected the heart from abnormal left ventricular remodelling and contractile dysfunction after TAC. We also observed less expression of hypertrophic markers, such as ANP and BNP, in TAC-operated PMCA4 −/− compared with WT. In contrast to the TAC model, the hypertrophic response was identical between PMCA4 −/− and WT after chronic swimming exercise. Analysis of signalling pathways in response to TAC showed that the Akt and Foxo3a signalling pathway may be regulated by PMCA4. As an initial step to generate a specific PMCA4 inhibitor, we screened the LOPAC library, containing medically optimised compounds. We have successfully identified a novel PMCA4 inhibitor (AP4), which has the IC50 of 150 nmol for PMCA4. In summary, our findings suggest a crucial and novel role of PMCA4 as a specific regulator of pathological, but not physiological, hypertrophy. In addition, the development of a novel inhibitor for PMCA4 might in the future be useable as the basis for novel therapeutic approaches in cardiac hypertrophy and failure.